Human trafficking and violence: Findings from the largest global dataset of trafficking survivors - Heidi Stöckl; Camilla Fabbri; Harry Cook; Claire Galez-Davis; Naomi Grant; Yuki Lo; Ligia Kiss; Cathy Zimmerman (Elsevier, 2021)
Background: Human trafficking is a recognized human rights violation, and a public health and global development issue. Violence is often a hallmark of human trafficking. This study aims to describe documented cases of violence amongst persons identified as victims of trafficking, examine associated factors throughout the trafficking cycle and explore prevalence of abuse in different labour sectors. Methods and findings: The IOM Victim of Trafficking Database (VoTD) is the largest database on human trafficking worldwide. This database is actively used across all IOM regional and country missions as a standardized anti-trafficking case-management tool. This analysis utilized the cases of 10,369 trafficked victims in the VoTD who had information on violence. Results: The prevalence of reported violence during human trafficking included: 54% physical and/or sexual violence; 50% physical violence; and 15% sexual violence, with 25% of women reporting sexual violence. Experiences of physical and sexual violence amongst trafficked victims were significantly higher amongst women and girls (AOR 2.48 (CI: 2.01,3.06)), individuals in sexual exploitation (AOR 2.08 (CI: 1.22,3.54)) and those experiencing other forms of abuse and deprivation, such as threats (AOR 2.89 (CI: 2.10,3.98)) and forced use of alcohol and drugs (AOR 2.37 (CI: 1.08,5.21)). Abuse was significantly lower amongst individuals trafficked internationally (AOR 0.36 (CI: 0.19,0.68)) and those using forged documents (AOR 0.64 (CI: 0.44,0.93)). Violence was frequently associated with trafficking into manufacturing, agriculture and begging (> 55%). Conclusions: An analysis of the world's largest data set on trafficking victims indicates that violence is indeed prevalent and gendered. While these results show that trafficking-related violence is common, findings suggest there are patterns of violence, which highlights that post-trafficking services must address the specific support needs of different survivors.